Systemic Approach Philosophy of Ecological (Environmental) Security in the Context of National Security - Ciszek, Mariusz (Studia Ecologiae et Bioethicae, 2016)
Ecological (environmental) security can be defined as a permanent state of no threats to environmental balance. The security understood that way is analyzed in the context of national security. National security is more and more often being described as a system. This publication assumes that no state will be able to maintain its integrity unless it provides an appropriate level of ecological security perceived as systemic environmental protection. A secure state is the one taking care of the natural environment. This approach results from the systems philosophy, promoted in the publication, concerning the perception of ecological security as one of the areas (subsystems) of the global national security system (supersystem). A proper condition of the natural environment framed by state borderlines is reflected in other system-related domains shaping the global national security system. The issues mentioned in the publication are going to be juxtaposed with the concept of the national security of Poland; still, these remarks are going to be of general nature, going beyond the context of Poland.